Phân tích phổ mật độ của tín hiệu nhiễu điện hóa trong ăn mòn đều thép cacbon thấp - Chiến, Nguyễn Văn; Cường, Lê Văn; Tĩnh, Nguyễn Trọng (Vietnam Journal of Chemistry, 2015)
One of modern approachs to analyze a random signal characteristics of electrochemical noise is estimated spectral power density and energy density of it, which is the energy distribution of the signal in the frequency domain. The analysis of the fluctuation spectrum electrode potential or electrochemical current appear in an electrochemical is an interesting development technique is concerned to monitor the beginnings and endings of a general corrosion. One of useful tools are the algorithm fast Fourier transform (FFT) and wavelet analysis (Wt)... have been applied spectral analysis of the electrochemical noise in the study of corrosion. This report presents the results of analysis of the electrochemical noise signal of the corrosive process through energy spectral density (ESD) and power spectral density (PSD) of current electrochemical noise. Corrosion process was studied by mild carbon steel electrodes in the 1 N H2SO4 and 0.1 M citric acid (C6H8O7) solutions in ambient conditions.